PERAN UNITED NATIONS DEVELOPMENT DALAM MEWUJUDKAN SUSTAINABLE DEVELOPMENT GOALS (SDGS) BIDANG PERDAMAIAN, KEADILAN, DAN KELEMBAGAAN YANG KUAT DI INDONESIA - Agnes Indriani Hasanah; Hayat Hayat; Suyeno Suyeno; Taufiq Rahman Ilyas; Afifudin Afifudin (Universitas Bina Taruna Gorontalo, 2024)
This research aims to explains the method used to analyze the implementation of the United Nations (Department of Economic and Social Sustainable Development) program in achieving the Sustainable Development Goals (SDGs), which is the global development agenda agreed upon by 193 UN member countries in 2015. The research method used is Systematic Literature Review (SLR), which involves the systematic identification, evaluation, and interpretation of evidence contained in scientific literature to answer specific research questions. The results of this research will help Indonesia achieve the SDGs in the fields of peace, justice and strong institutions, which is goal number 16 of the 17 SDGs goals. UNDP programs in Indonesia have an important role in supporting the achievement of the SDGs in the areas of peace, justice and institutions through various initiatives and projects that are in line with national and regional priorities. However, as the implementation of its programs is faced with various challenges and obstacles, such as the complexity of problems in the fields of peace, justice and institutions, lack of resources and uncertainty in funding. Efforts continue to be made to find innovative solutions and obtain further support from relevant parties